Long‐term dementia risk prediction by the LIBRA score: A 30‐year follow‐up of the CAIDE study. (6th December 2019) - Deckers, Kay; Barbera, Mariagnese; Köhler, Sebastian; Ngandu, Tiia; van Boxtel, Martin; Rusanen, Minna; Laatikainen, Tiina; Verhey, Frans; Soininen, Hilkka; Kivipelto, Miia; Solomon, Alina
Abstract : Objective: As no causal treatment for dementia is available yet, the focus of dementia research is slowly shifting towards prevention strategies. Therefore, this study aimed to examine the predictive accuracy of the "LIfestyle for BRAin Health" (LIBRA) score, a weighted compound score of 12 modifiable risk and protective factors, for dementia and mild cognitive impairment (MCI) in midlife and late‐life, and in individuals with high or low genetic risk based on presence of the apolipoprotein (APOE) ε4 allele. Methods: The LIBRA score was calculated for participants from the Finnish Cardiovascular Risk Factors, Aging and Dementia (CAIDE) population‐based study examined in midlife (n = 1024) and twice in late‐life (n = 604) up to 30 years later. Diagnoses of MCI and dementia were made according to established criteria. Cox proportional hazards models were used to assess the association between LIBRA and risk of dementia and MCI in models adjusted for sex and education (age as timescale). Results: Higher midlife LIBRA scores were related to higher risk of dementia (hazard ratio [HR] = 1.27; 95% confidence interval [CI], 1.13‐1.43) and MCI (unadjusted model: HR = 1.12; 95% CI, 1.03‐1.22) up to 30 years later. Higher late‐life LIBRA scores were related to higher risk of MCI (HR = 1.11; 95% CI, 1.00‐1.25), but not dementia (HR = 1.02; 95% CI, 0.84‐1.24). Higher late‐life LIBRA scores were related to higher dementia risk among apolipoprotein E (APOE) ε4 non‐carriers. Conclusions: Findings emphasize the importance of modifiable risk and protective factors for dementia prevention.